A Theoretical Framework on Customer Satisfaction in an Automotive Lubricant Market - Noor Aida Shazwani Abd Razak; Shariff Harun; Siti Norida Wahab (Information Management and Business Review, 2023)
Malaysia was reported to have the highest car ownership ratio in the ASEAN region, with 3.3 people per vehicle. As a result of this rapidly growing automotive sector, Malaysia experienced a rise in the demand for premium lubricants. Recognizing the fact that most automobile users would rather pay a mechanic or workshop to perform an oil change rather than do it themselves, hence, this study seeks to understand the antecedents that influence automotive lubricant consumer satisfaction. A content analysis approach is used in this study to discover potential antecedents of consumers' quality-of-service experiences. The SERVQUAL model is then employed as the theoretical foundation for investigating and synthesizing the antecedents. Five antecedents are addressed during the examination and discussion: tangibility, dependability, responsiveness, assurance, and empathy. In addition, five quality-of-service experience propositions are offered, and the framework developed in this conceptual study highlights the quality-of-service experience instigators. This study's conceptual nature provides preliminary insights into the quality-of-service experience in the automotive lubricant market. This study contributes to the body of knowledge by illuminating the antecedents that promote service quality, resulting in satisfied customers who will in turn stimulate the Malaysian automotive lubricant market, which can lead to a significant increase in the industry's contribution to Malaysia's gross domestic product (GDP) rate. The developed theoretical framework serves as a foundation for future empirical studies of quality-of-service experience.